Development of aptamer based colorimetric assay for whole blood glycated hemoglobin (HbA1c) estimation using gold nanoparticles - Rooma Devi; Aman Chauhan; Sandeep Yadav; Prabhat Kumar; C.S. Pundir (Biosensors and Bioelectronics: X, 2023)
Thiol-modified aptamer oligonucleotides containing gold nanoparticles (G@NPs) bound to glycated hemoglobin (HbA1c) with high affinity in whole blood samples. Aptamer thiol groups enhanced the stability of aptamers adsorbed on the surface of G@NPs. A detection strategy was used to visually confirm the presence of HbA1c and the absorbance of the colored compounds at selected wavelengths. Modified G@NPs are used in many colorimetric detection strategies due to their high extinction coefficient and strongly distance-dependent optical properties. In the present study, as the target analyte reports a method to prepare gold nanoparticle-bound purple aptamer aggregates that rapidly collapse into bluish red dispersed nanoparticles upon binding of HbA1c. HbA1c was detected in unpretreated whole blood after dilution at pH 7.4 and with UV-VIS double beam spectrophotometer with a lower limit of detection (LOD) (0.1 μM) and a much broader linear detection range (0.1 μM–100 μM). This current colorimetric method provides a rapid (7 min), accurate and high determination of whole blood HbA1c with minimal interference from uric acid, bovine serum albumin, hemoglobin, and glucose. The lower detection limit and broader linearity of aptamer-bound G@NPs hybrids improve the accuracy and precision of HbA1c measurements.